If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9+9x=27
We move all terms to the left:
9+9x-(27)=0
We add all the numbers together, and all the variables
9x-18=0
We move all terms containing x to the left, all other terms to the right
9x=18
x=18/9
x=2
| 9−z=-2z | | 10-8x=-2x=4x | | F(n)=(2n-1)² | | 6x-4x+10=22 | | 6x+3=3(x-5) | | 6t^2-11t+9=0 | | 2(3x+6)=90 | | 5b-12=5b+3 | | 5x-14+90+x+8=180 | | 11x-8=3x+24 | | (2x+6)+126+x=180 | | x+(x+950)*0.15=48233 | | x/2=1/2(×+8) | | 5{2b-6}=4b | | 120+2x+3x=180 | | 152+x+x=180 | | X^3-30x^2+249x-400=0 | | 156+x+108=180 | | W=180+1.5x | | 34x68=45 | | -120=180+1.5t | | x+(x+950)*0.15=48266 | | W=180+1.5t | | y/3+5=30 | | 15-3t=-3 | | 9-6(4u-11)=u+15 | | 0.92y=y-3 | | 6=3+3b | | 40x^2=180x | | h/16=4 | | 31-z=98 | | (3x-5)^2-(2x-3)^2=0 |